The Impact of One Book About Friendship in the Lives of Readers. (July 2022) - Gómez, Aitor; Puigvert, Lídia; Nazareno, Elías; López de Aguileta, Ane; Vidu, Ana; García-Carrión, Rocío
Research shows the benefits quality friendships have throughout humans' lives. Recent scientific literature focuses on social impact. However, the social impact of reading and dialoguing about a book about friendship is not explored. This study aims to analyze the impact of "Creative Friendships" in the lives of participants and their surroundings. Using communicative methodology, based on dialogical co-creation from the start, it includes 30 participants from diverse backgrounds and ages through individual interviews, a focus group and the observation of two dialogic seminars. Results show how reading and discussing the book impacted participants' views of beauty, goodness, truth, and freedom.